2013
DOI: 10.1371/journal.pone.0063419
|View full text |Cite
|
Sign up to set email alerts
|

HMGA1: A Master Regulator of Tumor Progression in Triple-Negative Breast Cancer Cells

Abstract: Emerging evidence suggests that tumor cells metastasize by co-opting stem cell transcriptional networks, although the molecular underpinnings of this process are poorly understood. Here, we show for the first time that the high mobility group A1 (HMGA1) gene drives metastatic progression in triple negative breast cancer cells (MDA-MB-231, Hs578T) by reprogramming cancer cells to a stem-like state. Silencing HMGA1 expression in invasive, aggressive breast cancer cells dramatically halts cell growth and results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
141
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(147 citation statements)
references
References 46 publications
(59 reference statements)
5
141
1
Order By: Relevance
“…HMGA1 is necessary for tumor-promoter-induced transformation and enhances tumor growth and invasion, which is opposite of the role of miR-142-3p [24,25,26,27,28]. Conversely, silencing of HMGA1 has been demonstrated to suppress tumor cell proliferation and invasion [29]. In this study, we identified HMGA1 as a functional target of miR-142-3p.…”
Section: Discussionmentioning
confidence: 90%
“…HMGA1 is necessary for tumor-promoter-induced transformation and enhances tumor growth and invasion, which is opposite of the role of miR-142-3p [24,25,26,27,28]. Conversely, silencing of HMGA1 has been demonstrated to suppress tumor cell proliferation and invasion [29]. In this study, we identified HMGA1 as a functional target of miR-142-3p.…”
Section: Discussionmentioning
confidence: 90%
“…In basal-like breast cancer subtype, Pegoraro et al indicated that HMGA1 was fundamental in sustaining stem cell and metastatic properties through cooperating with the Wnt/beta-catenin and Pin1/mutant p53 signaling pathways [14]. Moreover, Shah et al reported that HMGA1 is a master regulator of tumor progression in breast cancer by reprogramming cancer cells through stem cell transcriptional networks in triple-negative breast cancer cells [15]. As for HMGA1 expression in breast cancer, most studies published so far have been performed on cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HMGA1 is fundamental in sustaining stem cell and metastatic properties through cooperating with the Wnt/beta-catenin and Pin1/mutant p53 signaling pathways in basal-like breast cancer subtype [14]. In triple-negative breast cancer cells, HMGA1 is a master regulator of tumor progression in breast cancer by reprogramming cancer cells through stem cell transcriptional networks [15]. Although associations between HMGA1 expression and clinicopathological features including prognosis have been investigated in various human cancer such as lung cancer [16], colorectal cancer [17], liver cancer [18], pancreatic adenocarcinoma [19][20][21], and uveal melanomas [22], little is known about HMGA1 in breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…3 Emerging evidence suggests that master regulators, such as the high mobility group A1 (HMGA1) chromatin remodeling protein, orchestrates the assembly of Nuclear-factor kappa B (NF-kB) and transcription factor complexes to induce stem cell transcriptional networks and downstream signaling pathways that maintain CSCs. [3][4][5][6] Prior studies also suggest that Nuclear-factor kappa B (NF-kB) is hyperactive in MM and leukemic stem cells (Fig. 1).…”
Section: -2mentioning
confidence: 92%